Highly effective adsorption and passivation of Cd from wastewater and soil by MgO- and Fe3O4-loaded biochar nanocomposites - Ding, Hua; Liu, Jie; Li, Qibiao; Liu, Zhichen; Xia, Kai; Hu, Ling; Wu, Xiaoxu; Yan, Qian (Frontiers in Environmental Science, 2023)
The application of Fe -(BC-Fe) and Mg-modified (BC-Mg) biochar for the remediation of heavy-metal contaminated soil has been a research hotspot in recent years. It is critical to select suitable biochar under the same pollution condition. In this study, the biochars were characterized by FTIR, XRD and SEM. In addition, the adsorption and passivation effect of BC-Fe and BC-Mg was comprehensively evaluated through batch adsorption experiments and soil incubation experiments, and the effects on plant growth on Cd-contaminated soil were also illustrated by pot experiments.The Cd adsorption and passivation effects of MgO and Fe3O4 nanoparticles loaded biochar were compared through batch adsorption experiments and soil incubation experiments, and the effects on plant growth on Cd-contaminated soil were also illustrated by pot experiments. SEM, FTIR and XRD showed that MgO and Fe3O4 nanoparticles were successfully loaded on biochar surface. The Cd maximum adsorption of BC-Fe and BC-Mg were 52.63 and 66.23 mg g -1 , which were 9.05 and 7.19 times higher than the original biochar (7.32 mg g -1 ), respectively. Soil culture experiment showed that 5% BC-Fe and BC-Mg significantly reduced soil DTPA-Cd by 38.86% and 50.85% at 120 days, respectively. In addition, BC-Fe and BC-Mg promoted the conversion of acid soluble Cd to the oxidizable and residual states. Pot experiments revealedshowed that BC-Fe and BC-Mg reduced the Cd content in shoot of the maize by 3.97, and 6.09 times, respectively, and both significantly increased the dry and fresh weights in the shoot and root of the maize plants. Moreover, BC, BC-Fe and BC-Mg provided nutrients of plant growth to the soil and increased the activities of soil dehydrogenase, urease and peroxidase. The adsorption-passivation mechanism of BC-Fe on Cd mainly included electrostatic attraction while the adsorption-passivation mechanism of BC-Mg on Cd included precipitation and ion exchange. Results Overall, BC-Mg can be used as an efficient 2 This is a provisional file, not the final typeset article functional material for heavy metal pollution remediation, and this study provided guidance for the selection of passivator materials for soil heavy metal remediation..